Understanding the entrepreneurial capacity of university students: an empirical study at Milagro State University, Ecuador - D'Armas Regnault, Mayra; Fajardo Vaca, Ligia; Mejías-Acosta, Agustín; Noboa Romero, Pedro; Álvarez Baque, Wellington; Vidal-Silva, Cristian (Frontiers in Education, 2025)
Entrepreneurship is an essential driver of economic development, fostering innovation, job creation, and business growth. Universities play a crucial role in nurturing entrepreneurial capacity among students, making it imperative to identify and understand the factors influencing this capacity. This study investigates the determinants of entrepreneurial capacity among students at Milagro State University (UNEMI), utilizing the Theory of Planned Behavior (TPB) as a conceptual framework. A comprehensive measurement instrument was designed and administered to a sample of 2,570 students, and the data were analyzed using Structural Equation Modeling (SEM). The findings highlight that personal attitude and perceived behavioral control significantly influence students' entrepreneurial intentions, whereas subjective norms show no direct effect. These insights provide valuable guidance for the development of targeted policies and educational strategies to enhance the education of university entrepreneurship, ultimately contributing to regional economic development.